A method for preparing an aluminum-magnesium laminated composite material based on chemical copper plating pretreatment
Patent Information
- Application Number
- CN202611124598.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-28
AI Technical Summary
[0003]然而,现有基于SPS制备铝镁叠层复合材料的方案存在固有技术缺陷:在SPS瞬时高温场下,铝与铜的互扩散活化能显著低于镁与铜,导致Al-Cu界面反应速率远高于Mg-Cu界面,超薄纯铜箔会优先向铝侧快速扩散消耗,造成镁侧界面出现铜源匮乏问题,无法形成连续稳定的冶金结合层,使得镁侧始终是整个叠层结构的性能薄弱环节
(1)通过在镁合金基板双表面采用特定工艺化学置换镀铜,原位制备带有三维互通孔隙的薄铜层,在不增加中间铜箔厚度的前提下,为镁侧界面预置充足铜源,解决了传统工艺中铜元素单向向铝合金侧扩散、镁侧出现铜元素贫化的“铜饥饿”问题。多孔结构形成大量原子扩散通道,有效降低铜原子扩散阻力,使铜元素可同步、均衡地向铝、镁两侧基体扩散,各界面均形成连续稳定的梯度扩散冶金结合层;同时多孔铜层在烧结加压过程中可产生塑性形变,填充层间微小间隙,消除界面孔洞、裂纹等缺陷,大幅提升铝-铜、铜-镁界面的结合质量与整体性。
Smart Images

Figure CN122629455B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of metal layered composite material preparation technology, and particularly relates to a method for preparing aluminum-magnesium laminated composite materials based on chemical copper plating pretreatment. Background Technology
[0002] Aluminum-magnesium laminated composites combine the high strength and corrosion resistance of aluminum alloys with the low density and high specific strength of magnesium alloys, making them a core material for achieving lightweight structures in aerospace, rail transportation, and high-end equipment fields. Spark plasma sintering (SPS), with its rapid heating rate, short sintering cycle, and controllable interfacial reactions, has become the mainstream process for preparing heterogeneous metal laminated materials. In existing technologies, pure copper foil is commonly used as an intermediate transition layer between aluminum and magnesium. By blocking direct contact between aluminum and magnesium elements, the formation of hard and brittle Al-Mg intermetallic compounds is suppressed, thereby improving interfacial bonding performance.
[0003] However, existing methods for preparing aluminum-magnesium laminated composites based on SPS have inherent technical defects: under the instantaneous high-temperature field of SPS, the interdiffusion activation energy of aluminum and copper is significantly lower than that of magnesium and copper, resulting in a reaction rate at the Al-Cu interface that is much higher than that at the Mg-Cu interface. The ultrathin pure copper foil will preferentially diffuse and be consumed rapidly to the aluminum side, causing a copper source shortage problem at the magnesium side interface. As a result, a continuous and stable metallurgical bonding layer cannot be formed, making the magnesium side always the weak link in the performance of the entire laminated structure.
[0004] To compensate for insufficient copper supply on the magnesium side, the conventional approach in this field is to increase the thickness of the copper foil or add multiple layers of copper foil on one side, attempting to improve the copper supply on the magnesium side through a crude method of increasing the total amount of copper. However, such solutions simultaneously and significantly increase the total amount of copper on the aluminum side, resulting in the formation of an excessively thick Al-Cu hard and brittle intermetallic compound layer on the aluminum side. This leads to a decrease in the toughness of the aluminum side interface and a concentration of residual stress, resulting in a two-way interface performance imbalance problem of "improved bonding on the magnesium side and deterioration of aluminum side performance first." At the same time, the increased amount of copper foil significantly increases the overall weight of the component and the cost of raw materials, which violates the original intention of lightweight design of aluminum-magnesium laminated composite materials. In addition, adjusting the diffusion by increasing the sintering temperature and extending the holding time can cause secondary problems such as matrix grain growth and a decrease in overall mechanical properties, failing to solve the problem of diffusion rate mismatch at its root. Summary of the Invention
[0005] To address some or all of the technical problems existing in the prior art, this application provides a method for preparing aluminum-magnesium laminated composite materials based on chemical copper plating pretreatment.
[0006] This application provides a method for preparing aluminum-magnesium laminated composite materials based on chemical copper plating pretreatment, including the following steps: Step S1: Perform surface polishing pretreatment on the aluminum alloy substrate and magnesium alloy substrate respectively to remove the surface oxide layer and scratches; Step S2: Perform chemical displacement copper plating pretreatment on the polished magnesium alloy substrate to form a porous pre-plated copper layer with a thickness of 2~3μm in situ on the two surfaces to be bonded on the magnesium alloy substrate. Step S3: Stack the aluminum alloy substrate, pure copper foil, magnesium alloy substrate with porous pre-plated copper layer, pure copper foil, and aluminum alloy substrate in sequence to form a symmetrical five-layer stacked structure, so that the porous pre-plated copper layer on both sides of the magnesium alloy substrate is tightly bonded to the adjacent pure copper foil. Step S4: The assembled laminated structure is sintered as a whole using spark plasma sintering process to balance the diffusion rate of copper elements at each interface, so that the aluminum-copper and copper-magnesium interfaces form a dense metallurgical bond.
[0007] Preferably, in step S1, the surface polishing pretreatment specifically involves: sequentially polishing the substrate surface to be bonded with sandpaper of 400 grit, 800 grit, and 1000 grit to improve surface flatness.
[0008] Preferably, in step S2, the specific process of chemical displacement copper plating is as follows: first, the magnesium alloy substrate is activated, and then the activated magnesium alloy substrate is immersed in an acidic copper sulfate plating solution with a pH value of 2.0 and allowed to stand for 45 seconds at room temperature; after the reaction is completed, the magnesium alloy substrate is taken out, rinsed with deionized water, dehydrated with anhydrous ethanol, and dried to obtain a magnesium alloy substrate with a porous pre-plated copper layer on the surface.
[0009] Preferably, the activation process of the magnesium alloy substrate before immersion in the plating solution is as follows: the magnesium alloy substrate is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence to remove surface oil stains, and then immersed in a 5% (w / w) dilute sulfuric acid solution for activation for 30 seconds. After removal, it is rinsed with deionized water, dehydrated with anhydrous ethanol, and dried.
[0010] Preferably, in step S4, the process parameters for spark plasma sintering are: vacuum degree in the sintering furnace is less than 5 Pa, heating rate is 100℃ / min, sintering temperature is 400℃, axial pressure is 50MPa, and holding time is 10min.
[0011] Preferably, the thickness of the pure copper foil is 0.1 mm, and the thickness of the aluminum alloy substrate and the magnesium alloy substrate is 1 mm.
[0012] Preferably, the aluminum alloy substrate is a 7075 aluminum alloy substrate, and the magnesium alloy substrate is an AZ31 magnesium alloy substrate.
[0013] The method for preparing aluminum-magnesium laminated composite materials based on electroless copper plating pretreatment in this application has the following advantages and positive effects: (1) By chemically replacing copper on both surfaces of a magnesium alloy substrate using a specific process, a thin copper layer with three-dimensional interconnected pores is prepared in situ. Without increasing the thickness of the intermediate copper foil, a sufficient copper source is pre-placed for the magnesium-side interface, solving the "copper hunger" problem of unidirectional diffusion of copper to the aluminum alloy side and copper depletion on the magnesium side in the traditional process. The porous structure forms a large number of atomic diffusion channels, effectively reducing the diffusion resistance of copper atoms, allowing copper to diffuse synchronously and evenly to both aluminum and magnesium substrates. A continuous and stable gradient diffusion metallurgical bonding layer is formed at each interface. At the same time, the porous copper layer can undergo plastic deformation during sintering and pressurization, filling the tiny gaps between layers, eliminating defects such as interface pores and cracks, and greatly improving the bonding quality and integrity of the aluminum-copper and copper-magnesium interfaces.
[0014] (2) This application does not require thickening of copper foil or extension of sintering holding time, which avoids the problem of forming a thick layer of brittle intermetallic compound and reducing interface toughness due to excessive copper content on the aluminum side, and also prevents secondary defects such as coarsening of matrix grains and deterioration of mechanical properties caused by high temperature and long sintering. The whole process is simple and easy to control, and the amount of copper material used is small. While ensuring the high strength and high interface reliability of aluminum-magnesium laminated composite material, it retains the advantages of lightweight material and reduces raw material costs. Attached Figure Description
[0015] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only applicable to a further understanding of the embodiments of this application and constitute a part of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. In the drawings: Figure 1 This is a microstructure diagram of the chemical displacement copper plating of this application; Figure 2 This is an elemental distribution diagram of the aluminum-magnesium laminated composite material of this application, wherein Figure (a) represents Mg, Figure (b) represents Cu, and Figure (c) represents Al. Figure 3 This is a graph showing the interface energy dispersive spectroscopy results of the aluminum-magnesium laminated composite material of this application. Attached image description: 1-Mg matrix, 2-activated Mg surface, 3-three-dimensional interconnected pores, 4-in-situ grown porous copper layer. Detailed Implementation
[0017] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with specific embodiments and corresponding drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.
[0018] The method for preparing aluminum-magnesium laminated composite materials based on electroless copper plating pretreatment disclosed in this application is characterized by comprising the following steps: Step S1: Perform surface polishing pretreatment on the aluminum alloy substrate and magnesium alloy substrate respectively to remove the surface oxide layer and scratches.
[0019] The surface polishing pretreatment specifically involves using sandpaper of 400 grit, 800 grit, and 1000 grit to polish the substrate surface to be bonded in stages to improve surface smoothness.
[0020] Step S2: Perform chemical displacement copper plating pretreatment on the polished magnesium alloy substrate to form a porous pre-plated copper layer with a thickness of 2~3μm in situ on the two surfaces to be bonded on the magnesium alloy substrate.
[0021] The specific process of chemical displacement copper plating is as follows: First, the magnesium alloy substrate is activated by ultrasonic cleaning with anhydrous ethanol and deionized water to remove surface oil. Then, it is immersed in a 5% (w / w) dilute sulfuric acid solution for 30 seconds. After removal, it is rinsed with deionized water, dehydrated with anhydrous ethanol, and dried. Next, the activated magnesium alloy substrate is immersed in an acidic copper sulfate plating solution with a pH of 2.0 and allowed to stand at room temperature for 45 seconds. After the reaction is completed, the magnesium alloy substrate is removed, rinsed with deionized water, dehydrated with anhydrous ethanol, and dried to obtain a magnesium alloy substrate with a porous pre-plated copper layer on the surface.
[0022] This application uses an acidic copper sulfate system with a pH adjusted to 2.0 to complete the displacement copper plating. The displacement reaction occurs due to the higher reactivity of magnesium than copper. The overall reaction equation is Mg + Cu. 2+ =Mg 2+ +Cu; During the reaction, the magnesium matrix surface undergoes oxidative dissolution: Mg→Mg 2+ +2e - In solution, copper ions gain electrons on the magnesium-activated surface, reducing and precipitating elemental copper: Cu. 2+ +2e - →Cu; By controlling the short-term displacement reaction of 45s, elemental copper is only locally precipitated, without forming a complete and dense copper film. Ultimately, a thin copper layer with three-dimensional interconnected pores is generated in situ on both surfaces of the magnesium substrate. For example... Figure 1As shown, 1 is the Mg matrix, 2 is the activated Mg surface, 3 is the three-dimensional interconnected pores, and 4 is the in-situ grown porous copper layer.
[0023] This application describes a porous copper layer with three-dimensional interconnected pores generated in situ on both surfaces of a magnesium alloy substrate. This layer offers the following advantages: it provides a pre-placed copper source for the magnesium-side interface, continuously replenishing copper atoms during sintering to ensure sufficient copper content at the copper-magnesium interface and prevent copper depletion and starvation defects on the magnesium side; the three-dimensional interconnected pores provide numerous channels for copper atoms to diffuse into the magnesium matrix, significantly reducing diffusion resistance and enabling copper to diffuse synchronously and smoothly to both aluminum and magnesium sides, achieving balanced copper diffusion behavior at both interfaces; the porous structure can undergo plastic deformation under high temperature and pressure conditions, filling the microscopic gaps between the magnesium matrix and the copper foil, improving interlayer bonding tightness, reducing interface pores and cracks, and promoting the formation of a continuous and dense metallurgical bonding transition layer; and it achieves copper replenishment on the magnesium side without increasing the thickness of the intermediate copper foil, preventing the formation of excessively thick and brittle intermetallic compounds on the aluminum side due to excessive copper accumulation, thus ensuring interfacial bonding strength while improving the overall toughness and mechanical stability of the material.
[0024] Step S3: Stack the aluminum alloy substrate, pure copper foil, magnesium alloy substrate with porous pre-plated copper layer, pure copper foil, and aluminum alloy substrate in sequence to form a symmetrical five-layer stacked structure, so that the porous pre-plated copper layer on both sides of the magnesium alloy substrate is tightly bonded to the adjacent pure copper foil. Step S4: The assembled laminated structure is sintered as a whole using spark plasma sintering process to balance the diffusion rate of copper elements at each interface, so that the aluminum-copper and copper-magnesium interfaces form a dense metallurgical bond.
[0025] The process parameters for spark plasma sintering are as follows: vacuum degree in sintering furnace is less than 5 Pa, heating rate is 100℃ / min, sintering temperature is 400℃, axial pressure is 50MPa, and holding time is 10min.
[0026] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments.
[0027] The raw materials and formulation used in this embodiment are as follows: 7075 aluminum alloy sheet: solid circular sheet, 50mm in diameter × 1mm, 2 pieces; AZ31 magnesium alloy plate: solid circular plate, 50mm in diameter × 1mm, 2 pieces; Pure copper foil: 50mm diameter × 0.1mm, 2 pieces; Copper sulfate (CuSO4·5H2O): solid crystals, 50g; Concentrated sulfuric acid (H2SO4, 98%): liquid, 5 mL; Anhydrous ethanol (C2H5OH): Liquid, 500mL; Deionized water (H2O): Liquid, 2000 mL; The specific preparation steps are as follows: Surface polishing pretreatment: The surfaces of the 7075 aluminum alloy plate and AZ31 magnesium alloy plate to be bonded were successively polished using 400 grit, 800 grit, and 1000 grit sandpaper to remove impurities and processing scratches from the surface of the plates and improve the surface flatness.
[0028] AZ31 magnesium alloy plate chemical displacement copper plating pretreatment: (1) Cleaning and activation: The polished AZ31 magnesium alloy plate was ultrasonically cleaned with anhydrous ethanol and deionized water in sequence to remove surface oil stains; then the magnesium alloy plate was immersed in a 5% dilute sulfuric acid solution for 30 seconds to activate it, and then rinsed with deionized water, and then dehydrated and dried with anhydrous ethanol.
[0029] (2) Preparation of plating solution: Take 50g of copper sulfate pentahydrate, dissolve it in 1000mL of deionized water, and stir until completely dissolved; slowly add 5mL of 98% concentrated sulfuric acid and continue stirring to adjust the pH of the plating solution to 2.0.
[0030] (3) Displacement copper plating: The activated magnesium alloy plate is completely immersed in the prepared plating solution and allowed to stand for 45 seconds at room temperature (25±2℃). Through displacement reaction, a porous pre-plated copper layer with a thickness of 2~3μm is generated in situ on the two surfaces to be bonded of the magnesium alloy plate.
[0031] (4) Post-treatment: Take out the copper-plated magnesium alloy plate, rinse it with deionized water, then dehydrate it with anhydrous ethanol, and dry it in a 60℃ drying oven for later use.
[0032] Layered assembly: The 7075 aluminum alloy plate, pure copper foil, copper-plated AZ31 magnesium alloy plate, pure copper foil, and 7075 aluminum alloy plate are stacked in sequence to form a symmetrical five-layer stacked structure, ensuring that the porous pre-plated copper layer on both sides of the AZ31 magnesium alloy plate is tightly bonded to the adjacent pure copper foil.
[0033] Spark plasma sintering: (1) Place the assembled five-layer stack into a special SPS graphite mold; (2) Place the graphite mold containing the sample into the discharge plasma sintering furnace chamber and evacuate until the pressure inside the furnace is below 5 Pa. (3) Set the sintering process: heat up to 400℃ at a heating rate of 100℃ / min, apply 50MPa axial pressure after reaching the set temperature, and hold at 400℃ and 50MPa for 10min. (4) After the heat preservation and pressure preservation are completed, the sample is naturally cooled to room temperature with the furnace, and then the pressure is released and the sintered aluminum-magnesium laminated composite material is taken out.
[0034] Finished product cleaning: The sintered aluminum-magnesium laminated composite material was cleaned with anhydrous ethanol and then air-dried to obtain the finished product.
[0035] The aluminum-magnesium laminated composite material prepared in this embodiment was characterized by three aspects: microstructure observation, interface composition analysis, and room temperature mechanical property testing.
[0036] Microscopic morphological observation: The cross-sectional morphology of the Cu-Mg interface and the Al-Cu interface was observed using scanning electron microscopy. The results showed that the interfaces of each layer were tightly bonded, continuous and straight, without obvious pores, cracks and interlayer delamination defects, and the interface transition was uniform, which has a good metallurgical bonding foundation.
[0037] Interface component analysis: Energy-dispersive X-ray spectroscopy was used to perform elemental surface distribution and point-to-point energy dispersive spectroscopy quantitative analysis on the interfacial diffusion layer. (1) Elemental surface distribution analysis: Surface distribution maps of Mg, Cu, and Al were collected in the cross section (e.g., Figure 2 As shown in Figure (a), Mg is represented by Figure (b), Cu by Figure (c), and Al by Figure (c). The graphs reveal that Mg and Al are concentrated in the two side matrices, while Cu is stably and continuously distributed in the intermediate transition layer, with clear boundaries between the three layers. The three elements exhibit a continuous gradient diffusion distribution at the interface, without sharp boundaries of abrupt changes in element content. The copper layer is intact without any blank or depleted zones, and no copper-starved defects are observed on the magnesium side interface. Cu diffuses synchronously and smoothly into both the Mg and Al matrices, with uniform matching of diffusion zones on both sides, confirming sufficient interdiffusion of elements at the interface and the formation of a metallurgically bonded transition layer.
[0038] (2) Quantitative analysis by fixed-point energy dispersive spectroscopy: Energy spectra are collected at fixed points in the copper-magnesium diffusion interface region (e.g., Figure 3As shown in the figure, quantitative detection results indicate that the mass fraction of Mg in this region is 59.3%, Cu is 24.5%, Al is 13.8%, and Zn is 2.3%. This data suggests that a large amount of both magnesium matrix elements and copper elements exist simultaneously in the interface transition zone, and sufficient interdiffusion has occurred between them, forming a stable solid solution-type diffusion bonding layer. The copper content in this region reaches 24.5%, which is sufficient, proving that there is no copper depletion problem at the magnesium side interface. This effectively solves the problem of copper starvation at the magnesium side interface during SPS sintering and verifies the copper source compensation effect of pre-plated copper on the magnesium surface. The detected Al and Zn elements originate from the alloy composition of AZ31 magnesium alloy and 7075 aluminum alloy, respectively, further confirming that multi-element cross-layer diffusion has occurred at the interface, resulting in sufficient metallurgical bonding.
[0039] Room temperature tensile mechanical property testing: The composite material was processed into a tensile standard specimen according to the standard for metal tensile test specimens, and a room temperature uniaxial tensile test was carried out using a microcomputer-controlled electronic universal testing machine. During the test, it was observed that the aluminum-magnesium laminated composite material prepared in this embodiment did not fracture at the copper-magnesium interface, indicating reliable interfacial bonding.
[0040] In summary, this application utilizes a specific process for chemical displacement copper plating on both surfaces of a magnesium alloy substrate to prepare a thin copper layer with three-dimensional interconnected pores in situ. This provides a sufficient copper source for the magnesium-side interface without increasing the thickness of the intermediate copper foil, solving the "copper starvation" problem in traditional processes where copper diffuses unidirectionally to the aluminum alloy side while the magnesium side suffers from copper depletion. The porous structure forms numerous atomic diffusion channels, effectively reducing the diffusion resistance of copper atoms, allowing copper to diffuse synchronously and evenly to both the aluminum and magnesium substrates. Each interface forms a continuous and stable gradient diffusion metallurgical bonding layer. Simultaneously, the porous copper layer undergoes plastic deformation during sintering and pressurization, filling the tiny gaps between layers and eliminating defects such as interface pores and cracks, significantly improving the bonding quality and integrity of the aluminum-copper and copper-magnesium interfaces.
[0041] This application eliminates the need for thickening the copper foil or extending the sintering holding time, thus avoiding the problems of thick, brittle intermetallic compounds forming on the aluminum side due to excessive copper content and reduced interfacial toughness. It also prevents secondary defects such as matrix grain coarsening and mechanical property degradation caused by high-temperature, long-term sintering. The entire process is simple and easy to control, using less copper. While ensuring the high strength and high interfacial reliability of the aluminum-magnesium laminated composite material, it retains the material's lightweight advantages and reduces raw material costs.
[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.
Claims
1. A method for preparing aluminum-magnesium laminated composite materials based on electroless copper plating pretreatment, characterized in that, Includes the following steps: Step S1: Perform surface polishing pretreatment on the aluminum alloy substrate and magnesium alloy substrate respectively to remove the surface oxide layer and scratches; Step S2: Perform chemical displacement copper plating pretreatment on the polished magnesium alloy substrate to form a porous pre-plated copper layer with a thickness of 2~3μm in situ on the two surfaces to be bonded on the magnesium alloy substrate. Step S3: Stack the aluminum alloy substrate, pure copper foil, magnesium alloy substrate with porous pre-plated copper layer, pure copper foil, and aluminum alloy substrate in sequence to form a symmetrical five-layer stacked structure, so that the porous pre-plated copper layer on both sides of the magnesium alloy substrate is tightly bonded to the adjacent pure copper foil. Step S4: The assembled laminated structure is sintered as a whole using spark plasma sintering process to balance the diffusion rate of copper elements at each interface, so that the aluminum-copper and copper-magnesium interfaces form a dense metallurgical bond.
2. The method for preparing aluminum-magnesium laminated composite material based on electroless copper plating pretreatment according to claim 1, characterized in that, In step S1, the surface polishing pretreatment specifically involves: sequentially polishing the substrate surface to be bonded with sandpaper of 400 grit, 800 grit, and 1000 grit to improve surface flatness.
3. The method for preparing aluminum-magnesium laminated composite material based on electroless copper plating pretreatment according to claim 1, characterized in that, In step S2, the specific process of chemical displacement copper plating is as follows: first, the magnesium alloy substrate is activated, and then the activated magnesium alloy substrate is immersed in an acidic copper sulfate plating solution with a pH value of 2.0 and allowed to stand for 45 seconds at room temperature. After the reaction is completed, the magnesium alloy substrate is taken out, rinsed with deionized water, dehydrated with anhydrous ethanol, and dried to obtain a magnesium alloy substrate with a porous pre-plated copper layer on the surface.
4. The method for preparing aluminum-magnesium laminated composite material based on electroless copper plating pretreatment according to claim 3, characterized in that, The activation process of the magnesium alloy substrate before immersion in the plating solution is as follows: the magnesium alloy substrate is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence to remove surface oil stains, and then immersed in a 5% (w / w) dilute sulfuric acid solution for 30 seconds for activation. After removal, it is rinsed with deionized water, dehydrated with anhydrous ethanol, and dried.
5. The method for preparing aluminum-magnesium laminated composite material based on electroless copper plating pretreatment according to claim 1, characterized in that, In step S4, the process parameters for spark plasma sintering are as follows: the vacuum degree inside the sintering furnace is less than 5 Pa, the heating rate is 100℃ / min, the sintering temperature is 400℃, the axial pressure is 50MPa, and the holding time is 10min.
6. The method for preparing aluminum-magnesium laminated composite material based on electroless copper plating pretreatment according to claim 1, characterized in that, The thickness of the pure copper foil is 0.1 mm, and the thickness of the aluminum alloy substrate and the magnesium alloy substrate is 1 mm.
7. The method for preparing aluminum-magnesium laminated composite material based on electroless copper plating pretreatment according to claim 1, characterized in that, The aluminum alloy substrate is a 7075 aluminum alloy substrate, and the magnesium alloy substrate is an AZ31 magnesium alloy substrate.
Citation Information
Patent Citations
Preparation method of magnesium / aluminum-based laminated composite plate
CN108188523A
Preparation method of high-strength Zn / Cu / Mg layered composite material
CN117698223A